A negative electrode slurry and a method for preparing the same
Patent Information
- Application Number
- CN202611225669.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]上述钴酸锂的制备方法还存在制备成本较高,制备方法复杂,且制备得到的钴酸锂作为电池材料时循环性能有待进一步提高等问题
本申请提供的正极用底涂浆料的制备方法操作简单,在勃姆石+碳纳米管底涂浆料中引入特定的抗氧化剂和分散剂,有效提高了底涂浆料的稳定性和分散性;通过在铝箔上涂覆所述底涂浆料,能够大幅度改善高电压钴酸锂电池的循环性能。
Smart Images

Figure CN123017970A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a positive electrode primer slurry, its preparation method and application. Background Technology
[0002] Currently, lithium cobalt oxide materials on the market are being developed towards higher voltage and higher rate performance. However, under high voltage, trace amounts of acid (such as HF) and active oxygen in the electrolyte can corrode the aluminum foil, affecting the performance of the battery.
[0003] CN114074957A discloses a method for preparing titanium-doped high-voltage lithium cobalt oxide precursor, comprising the following steps: (1) preparing surface-modified amino graphene; (2) preparing titanium-doped lithium cobalt oxide precursor seed crystals; (3) preparing surface-modified monolayer titanium-doped lithium cobalt oxide precursor seed crystals; (4) preparing doped lithium cobalt oxide precursor; (5) preparing high-voltage lithium cobalt oxide; (6) preparing surface-modified self-assembled metal-organic framework compound monolayer film coating high-voltage lithium cobalt oxide; (7) preparing oxide coating high-voltage lithium cobalt oxide; (8) preparing titanium nitride and oxide coating high-voltage lithium cobalt oxide.
[0004] CN113044891A discloses a method for preparing surface-grafted high-voltage lithium cobalt oxide, comprising the following operations: S1, uniformly mixing and pre-crosslinking cobalt-containing material A, graft material B, and grafting aid C, followed by lithium enrichment treatment to obtain product D; or, uniformly mixing and pre-crosslinking cobalt-containing material A, graft material B, and grafting aid C to obtain product D; wherein, the cobalt-containing material A and / or graft material B undergo lithium enrichment treatment; S2, heating product D in air or an oxidizing atmosphere to perform a solid-state sintering reaction to obtain surface-grafted high-voltage lithium cobalt oxide with graft material B grafted onto its surface; wherein graft material B is a layered nickel-based material.
[0005] The above-mentioned methods for preparing lithium cobalt oxide also have problems such as high preparation cost, complex preparation methods, and the need to further improve the cycle performance of the prepared lithium cobalt oxide when used as a battery material. Summary of the Invention
[0006] In view of the problems existing in the prior art, this application provides a cathode primer slurry, its preparation method, and its application. It utilizes boehmite and carbon nanotubes in synergistic action with specific antioxidants and dispersants to effectively suppress the corrosion of aluminum foil by trace amounts of moisture and active oxygen in the electrolyte of lithium cobalt oxide under high operating voltages, thereby improving the stability and dispersibility of the primer slurry and ultimately increasing the cycle life of lithium cobalt oxide batteries. The preparation method is simple to operate, requiring no complex operations such as high-temperature calcination, and has low requirements for preparation equipment and low preparation cost.
[0007] To achieve this objective, the following technical solution is adopted in this application: In a first aspect, this application provides a method for preparing a primer slurry for a positive electrode, the method comprising the following steps: (1) Mix the adhesive with the organic solvent to obtain the adhesive solution; (2) Boehmite, antioxidant, dispersant and organic solvent are mixed to obtain boehmite dispersion; the antioxidant includes tert-butylhydroquinone and / or 2,5-di-tert-butylhydroquinone; the dispersant includes any one or a combination of at least two of monoisopropanolamine, diisopropanolamine or triisopropanolamine. (3) Mix the adhesive solution, boehmite dispersion and carbon nanotubes, and stir to obtain a base coating slurry for the positive electrode; Steps (1) and (2) are not in any particular order.
[0008] In the preparation method of the cathode primer slurry described in this application, boehmite, a raw material, not only inhibits the corrosion of aluminum foil by trace amounts of moisture and active oxygen in the electrolyte under high operating voltage (lithium salt LiPF6 readily reacts with water to generate highly corrosive HF, while boehmite γ-AlOOH + 3HF → AlF3 + 2H2O), thus preventing rapid capacity decay of lithium cobalt oxide batteries, but also, the nano-scale boehmite primer coating has abundant nanopores and a large specific surface area, which can improve the liquid retention and absorption performance of lithium cobalt oxide batteries, and is beneficial to the stable migration of lithium ions. The carbon nanotubes intertwine in the boehmite matrix to form a three-dimensional conductive network framework, which can effectively inhibit the shedding of active material caused by changes in particle volume during long-term cycling. The phenolic hydroxyl groups carried by the antioxidant can effectively capture peroxide free radicals and alkyl free radicals generated during the slurry preparation and coating process of oil-based slurries, terminating the chain oxidation reaction, while inhibiting the aging and degradation of the binder and the increase in slurry viscosity, thereby improving the stability of the slurry. Furthermore, the antioxidant adsorbs on the surface of carbon nanotubes, isolating the functional groups on the carbon nanotube surface from oxygen, thus maintaining the conductivity of the carbon nanotubes without decay and preventing blockage of conductive pathways. The dispersant effectively regulates the pH of the slurry system to remain stable in the weakly alkaline range, preventing boehmite from hydrolyzing and agglomerating in acidic environments. On the other hand, its hydrophobic carbon chains form a solvated adsorption layer with the oil phase solvent, generating a steric hindrance effect that can prevent the agglomeration and sedimentation of boehmite and CNT particles for a long time, improving the shelf life of the slurry. Therefore, the primer slurry prepared in this application has high stability and high dispersibility, which can effectively improve the cycle life of lithium cobalt oxide batteries.
[0009] The dispersant described in this application includes any one or a combination of at least two of monoisopropanolamine, diisopropanolamine, or triisopropanolamine, wherein typical but non-limiting combinations include a combination of monoisopropanolamine and diisopropanolamine, a combination of triisopropanolamine and monoisopropanolamine, or a combination of diisopropanolamine and triisopropanolamine.
[0010] In some embodiments, the adhesive in step (1) comprises polyvinylidene fluoride.
[0011] In some embodiments, the organic solvent in step (1) includes any one or a combination of at least two of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide, wherein typical but non-limiting combinations include a combination of N-methylpyrrolidone and N,N-dimethylformamide, a combination of N,N-dimethylacetamide and dimethyl sulfoxide or a combination of N-methylpyrrolidone and dimethyl sulfoxide.
[0012] In some embodiments, the solid content of the positive electrode primer slurry in step (3) is 20wt%~22wt%, for example, it can be 20.0wt%, 20.4wt%, 20.8wt%, 21.2wt%, 21.6wt% or 22.0wt%, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0013] The viscosity is 200~400 mPa·s, for example, it can be 200 mPa•s, 240 mPa•s, 280 mPa•s, 320 mPa•s, 360 mPa•s or 400 mPa•s, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0014] In some embodiments, the mass ratio of the binder, boehmite, and carbon nanotubes is 6:(92~93):(1~2), for example, it can be 6:92:1, 6:92:1.2, 6:92.5:1.5, 6:92.5:1.8, 6:93:1, or 6:93:2, etc., but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0015] In some embodiments, the antioxidant accounts for 0.2% to 0.3% of the total mass of the primer slurry, for example, it may be 0.20%, 0.22%, 0.24%, 0.26%, 0.28% or 0.30%, etc., but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0016] In some embodiments, the mass of the dispersant accounts for 0.3% to 0.4% of the total mass of the primer slurry, for example, it may be 0.30%, 0.32%, 0.34%, 0.36%, 0.38% or 0.40%, etc., but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0017] As a technical solution of this application, the preparation method includes the following steps: (1) Mix the adhesive with the organic solvent to obtain the adhesive solution; (2) Boehmite, antioxidant, dispersant and organic solvent are mixed to obtain boehmite dispersion; the antioxidant includes tert-butylhydroquinone and / or 2,5-di-tert-butylhydroquinone; the dispersant includes any one or a combination of at least two of isopropanolamine, diisopropanolamine or triisopropanolamine; the binder includes polyvinylidene fluoride; the organic solvent includes any one or a combination of at least two of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide; (3) Mix the adhesive solution, boehmite dispersion and carbon nanotubes, and stir to obtain a base coating slurry for the positive electrode; wherein, steps (1) and (2) are not in any particular order; The solid content of the primer slurry is 20wt%~22wt%, and the viscosity is 200~400mPa•s; the mass ratio of the binder, boehmite, and carbon nanotubes is 6:(92~93):(1~2); the antioxidant accounts for 0.2%~0.3% of the total mass of the primer slurry; and the dispersant accounts for 0.3%~0.4% of the total mass of the primer slurry.
[0018] Secondly, this application also provides a primer slurry for a positive electrode, which is obtained by the preparation method of the primer slurry for a positive electrode as described in the first aspect.
[0019] The primer slurry described in this application is applied to both sides of the aluminum foil, which can effectively suppress the corrosion of the aluminum foil by trace amounts of moisture and active oxygen in the electrolyte under high operating voltage, avoid rapid capacity decay of lithium cobalt oxide, and ensure that the lithium cobalt oxide battery has a high cycle life.
[0020] Thirdly, this application also provides a positive current collector, which includes an aluminum foil and a positive electrode primer and a positive electrode slurry as described in the second aspect, which are sequentially coated on the aluminum foil.
[0021] This application does not impose detailed limitations on the cathode slurry; conventional cathode slurries in the art can be used.
[0022] Fourthly, this application also provides a positive electrode sheet, said positive electrode sheet comprising the positive current collector as described in the third aspect.
[0023] Fifthly, this application also provides a lithium cobalt oxide battery, the lithium cobalt oxide battery comprising the positive electrode sheet as described in the fourth aspect.
[0024] Compared with the prior art, this application has at least the following beneficial effects: The preparation method of the positive electrode primer slurry provided in this application is simple to operate. By introducing specific antioxidants and dispersants into the boehmite + carbon nanotube primer slurry, the stability and dispersibility of the primer slurry are effectively improved. By coating the primer slurry on aluminum foil, the cycle performance of high-voltage lithium cobalt oxide batteries can be significantly improved. Attached Figure Description
[0025] Figure 1 This is an SEM image of the base coating aluminum foil obtained by coating the base coating slurry prepared in Example 1 of this application onto aluminum foil. Detailed Implementation
[0026] The technical solution of this application will be further described below with reference to the accompanying drawings and specific embodiments.
[0027] The present application is described in further detail below. However, the examples below are merely simplified examples and do not represent or limit the scope of protection of the present application. The scope of protection of the present application shall be determined by the claims.
[0028] Example 1 This embodiment provides a method for preparing a primer slurry for a positive electrode, the method comprising the following steps: (1) Mix the adhesive polyvinylidene fluoride with the organic solvent N-methylpyrrolidone to obtain an adhesive solution; (2) Boehmite, antioxidant tert-butylhydroquinone, dispersant diisopropanolamine and organic solvent N-methylpyrrolidone were mixed to obtain a boehmite dispersion; (3) Mix the adhesive solution, boehmite dispersion and carbon nanotubes, and stir to obtain a base coating slurry for the positive electrode; wherein, steps (1) and (2) are not in any particular order; The primer has a solid content of 21 wt% and a viscosity of 300 mPa•s; the mass ratio of the binder, boehmite, and carbon nanotubes is 6:92.5:1.2; the antioxidant accounts for 0.25% of the total mass of the primer; and the dispersant accounts for 0.35% of the total mass of the primer.
[0029] Example 2 This embodiment provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1, except that the mass ratio of binder, boehmite and carbon nanotubes is 6:91:1.2.
[0030] Example 3 This embodiment provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1, except that the mass ratio of binder, boehmite and carbon nanotubes is 6:94:1.2.
[0031] Example 4 This embodiment provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1, except that the antioxidant accounts for 0.1% of the total mass of the primer slurry.
[0032] Example 5 This embodiment provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1, except that the antioxidant accounts for 0.4% of the total mass of the primer slurry.
[0033] Example 6 This embodiment provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1, except that the mass of the dispersant accounts for 0.2% of the total mass of the primer slurry.
[0034] Example 7 This embodiment provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1, except that the mass of the dispersant accounts for 0.5% of the total mass of the primer slurry.
[0035] Comparative Example 1 This comparative example provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1 except that boehmite is not added.
[0036] Comparative Example 2 This comparative example provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1 except that carbon nanotubes are not added.
[0037] Comparative Example 3 This comparative example provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as in Example 1 except that no dispersant and antioxidant are added.
[0038] Comparative Example 4 This comparative example provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as that in Example 1, except that no dispersant is added.
[0039] Comparative Example 5 This comparative example provides a method for preparing a primer slurry for a positive electrode. The preparation method is the same as that in Example 1, except that no antioxidant is added.
[0040] The primer slurry prepared in the above examples and comparative examples was coated on both sides of a 12μm aluminum foil at a coating speed of 40m / min and a drying temperature of 130℃. The areal density of a single layer was controlled at 4.0g / m². 2 This yields a base-coated aluminum foil.
[0041] The SEM image of the base coating aluminum foil obtained by coating the base coating slurry prepared in Example 1 onto aluminum foil using the method described above is shown below. Figure 1 As shown. From Figure 1 It can be seen that AlOOH particles and one-dimensional carbon nanotubes achieve uniform composite. The boehmite staggered stack adsorbs free fluoride in the system, inhibiting oxygen evolution of lithium cobalt oxide, cobalt dissolution, and corrosion of aluminum current collectors at high potentials; linear CNTs interspersed in the gaps between boehmite particles form a three-dimensional conductive network, which compensates for the increase in interfacial impedance caused by the insulating properties of boehmite, while buffering the volume stress of charging and discharging, preventing the coating from cracking and peeling off.
[0042] Preparation of positive electrode slurry: High-voltage LCO material was selected as the positive electrode active material, polyvinylidene fluoride (Sowe 5130) was selected as the binder, and Super P (Swiss Temico) was selected as the conductive agent. The active material: binder: conductive agent were mixed at a mass ratio of 96.7:1.3:2. After being mixed evenly, the mixture was coated on the base aluminum foil and dried in a vacuum drying oven at 140℃ for 1 hour.
[0043] Preparation of negative electrode slurry: Graphite G9 (Jiangxi Zichen) was selected as the negative electrode active material, CMC and SBR were selected as the binders, and Super P (Swiss Temico) was selected as the conductive agent. The G9:SP:SBR:CMC mass ratio was 95.0:2.5:1.7:0.8. After mixing evenly, the mixture was coated on an 8μm copper foil and dried in a vacuum drying oven at 120℃ for 1h to obtain the negative electrode sheet.
[0044] The baked electrode sheets are rolled, slit, die-cut, assembled, injected with electrolyte, and subjected to capacity testing to obtain a soft-pack battery.
[0045] Comparative Example 6 This comparative example provides an aluminum foil without a base coating slurry, which is used to prepare a soft-pack battery according to the above method.
[0046] The pouch cells prepared in the above embodiments and comparative examples were subjected to charge-discharge tests using a charge-discharge tester, with a voltage range of 3.0~4.35V. The number of cycles was 100, 300, and 500, and the discharge current was 1C. The results of the capacity retention rates after 100 cycles, 300 cycles, and 500 cycles are shown in Table 1. In Table 1, " / " indicates that there is no data.
[0047] Comparative Example 2, due to the absence of carbon nanotubes, exhibits infinite resistance, making it impossible to assess its cycling performance.
[0048] As can be seen from Table 1: (1) The method for preparing the positive electrode undercoating slurry provided in this application prepares an undercoating slurry that is coated on aluminum foil. The final battery prepared can achieve a capacity retention rate of 97.1% after 100 cycles, 94.7% after 300 cycles, and 91.5% after 500 cycles, which greatly improves the cycle performance of high-voltage lithium cobalt oxide batteries. (2) As can be seen from the comparison between Example 1 and Examples 2-3, the boehmite in the positive electrode undercoating slurry of Example 2 is of low quality and cannot effectively suppress the corrosion of aluminum foil by trace amounts of water and active oxygen in the electrolyte under high working voltage, resulting in rapid capacity decay of lithium cobalt oxide battery; the boehmite in the positive electrode undercoating slurry of Example 3 is of high quality, which will lead to excessive solid content, poor slurry fluidity, microcracks will be generated during the drying process of the undercoating slurry, and the brittle coating is prone to powdering during subsequent rolling, thus affecting the safe use of battery. (3) A comparison of Examples 1 and 4-5 shows that the amount of antioxidant added in the cathode primer slurry of Example 4 is relatively small, which means that some of the peroxide free radicals and alkyl free radicals generated during the slurry preparation and coating process cannot be captured in time, and will re-initiate the chain cross-linking reaction, resulting in an abnormal increase in slurry viscosity after standing. The cycle performance of the battery prepared in the end is lower than that of Example 1. The amount of antioxidant added in the cathode primer slurry of Example 5 is relatively large, which means that the antioxidant forms a thicker non-oxidizing layer on the surface of the carbon nanotubes. The conductive organic coating layer leads to an increase in the resistivity of the electrode, which in turn affects the cycle performance of the battery; (3) As can be seen from the comparison between Example 1 and Examples 6-7, the amount of dispersant added in the positive electrode base coating slurry of Example 6 is relatively small, and the boehmite hydrolyzes and agglomerates in an acidic environment, resulting in uneven coating density of the positive electrode base coating slurry. The cycle performance of the battery prepared in the end is lower than that of Example 1; The amount of dispersant added in the positive electrode base coating slurry of Example 7 is relatively large, which leads to a shortening of the effective spatial steric distance between particles and secondary agglomeration. (4) As can be seen from the comparison between Example 1 and Comparative Examples 1, 3 to 6, the battery prepared by not adding boehmite, dispersant and antioxidant to the positive electrode base coating slurry of Comparative Examples 1, 3 to 5 will result in a significant reduction in the cycle performance of the prepared battery. However, the battery prepared by Comparative Example 6 with aluminum foil without base coating slurry has better cycle performance.
[0049] The primer slurries prepared in the above examples and comparative examples were sealed and placed in a clean flange container. The viscosity and solid content of the upper slurry were tested for the slurry before and after 10 days of standing. The results are shown in Table 2. As can be seen from Table 2: (1) The preparation method of the positive electrode primer slurry provided in this application introduces specific antioxidants and dispersants into the boehmite + carbon nanotube primer slurry, which effectively improves the stability and dispersibility of the primer slurry. The viscosity of the slurry before standing is 315.2 mPa•s, and the viscosity of the slurry after standing for 10 days is 320.3 mPa•s. The solid content of the upper slurry after standing for 10 days also does not change significantly. (2) As can be seen from the comparison between Example 1 and Examples 2 to 7, when the mass of boehmite, antioxidant and dispersant in the positive electrode primer slurry exceeds the range defined in this application, the viscosity of the primer slurry will be higher than that in Example 1. The viscosity of the slurry after standing for 10 days will increase significantly. Moreover, the solid content of the upper slurry will decrease, indicating that the stability of the primer slurry will decrease. (3) As can be seen from the comparison between Example 1 and Comparative Examples 1 to 5, the absence of boehmite, carbon nanotubes, dispersants and antioxidants, or the absence of dispersants or antioxidants in the positive electrode primer slurry will result in a serious deterioration in the stability and dispersibility of the primer slurry. The viscosity of the slurry after standing for 10 days will increase significantly, and the solid content of the upper slurry will also decrease significantly.
[0050] It is hereby declared that the above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.
Claims
1. A method for preparing a primer slurry for a positive electrode, characterized in that, The preparation method includes the following steps: (1) Mix the adhesive with the organic solvent to obtain the adhesive solution; (2) Boehmite, antioxidant, dispersant and organic solvent are mixed to obtain boehmite dispersion; the antioxidant includes tert-butylhydroquinone and / or 2,5-di-tert-butylhydroquinone; the dispersant includes any one or a combination of at least two of monoisopropanolamine, diisopropanolamine or triisopropanolamine. (3) Mix the adhesive solution, boehmite dispersion and carbon nanotubes, and stir to obtain a base coating slurry for the positive electrode; Steps (1) and (2) are not in any particular order.
2. The preparation method according to claim 1, characterized in that, The adhesive in step (1) includes polyvinylidene fluoride.
3. The preparation method according to claim 1 or 2, characterized in that, The organic solvent in step (1) includes any one or a combination of at least two of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide.
4. The preparation method according to any one of claims 1 to 3, characterized in that, The solid content of the positive electrode primer slurry in step (3) is 20wt%~22wt%, and the viscosity is 200~400mPa·s.
5. The preparation method according to any one of claims 1 to 4, characterized in that, The mass ratio of the binder, boehmite, and carbon nanotubes is 6:(92~93):(1~2).
6. The preparation method according to any one of claims 1 to 5, characterized in that, The antioxidant accounts for 0.2% to 0.3% of the total mass of the primer slurry; And / or, the mass of the dispersant accounts for 0.3% to 0.4% of the total mass of the primer slurry.
7. A primer slurry for a positive electrode, characterized in that, The primer slurry is obtained by the preparation method of the positive electrode primer slurry as described in any one of claims 1 to 6.
8. A positive electrode current collector, characterized in that, The positive current collector includes an aluminum foil and a positive electrode primer and a positive electrode slurry as described in claim 7, which are sequentially coated on the aluminum foil.
9. A positive electrode sheet, characterized in that, The positive electrode includes the positive current collector as described in claim 8.
10. A lithium cobalt oxide battery, characterized in that, The lithium cobalt oxide battery includes the positive electrode as described in claim 9.
Citation Information
Patent Citations
Preparation method of surface grafting type high-voltage lithium cobalt oxide, surface grafting type high-voltage lithium cobalt oxide and application of surface grafting type high-voltage lithium cobalt oxide
CN113044891A
